Establishing critical success factors for project management best practices in sustainable housing in Malaysia. - Bakar, Abu Hassan Abu; Awang, Aidah (2008)

(untitled)
This paper is attempt to establish a theoretical framework for project management best practices in sustainable housing development. Effective management of projects is becoming increasingly important for sustainable housing to remain competitive in today’s dynamic business environment. The objective of this paper is to establish success factors for project management best practices in the sustainable housing development in Malaysia. Review on past literature on the subject were carried out to build the existing research works on the area and to establish success factors of project management best practices. At the end of this paper, a new area of managing sustainable housing for future direction of this research was identified. A list of critical success factors for project management best practices for sustainable housing development in Malaysia was established.